PERILAKU SADARI REMAJA PUTRI MELALUI PENDIDIKAN KESEHATAN DI SMK 1 MUHAMMADIYAH LAMONGAN - Sulistiyowati, Sulistiyowati (Unusa Press, 2017)
Breast cancer incidence is still very high; therefore SADARI would be more effective if it is done as early as possible to determine abnormalities. Health education is one effort to make adolescents realizing to do SADARI. The aim of this research is to analyze the impact of health education on breast self-examination behavior in female adolescent. Research design used is One-Group Pretest-Posttest design using simple random sampling obtaining sample of 49 female adolescents at SMK Muhammadiyah 1 Lamongan in April 2016. Data were collected using checklist with the observation method and analyzed using Chi-Square. The results showed that before being given health education, 93.9% of female adolescents made mistakes in doing SADARI and after being given health education, 69.4% of female adolescents made mistakes in doing SADARI. There are differences in doing SADARI of female adolescents in eleventh grade before and after being given health education concluded from this data X 2 = 7,243 and p = 0.007. It can be concluded that the promotion of health education is very influential to improve SADARI in female adolescents. It can improve their knowledge and it can be applied in the examination and early detection of breast cancer.